Can cognitive behavioral-therapy increase the quality of life and self-efficacy in rheumatoid arthritis patients? - A'yun, Rahmania Qurrota; Hartini, Nurul (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Rheumatoid arthritis is a chronic autoimmune illness rarely found in Indonesia. The sufferers mostly are women. This illness affects both the physical and psychological conditions of the sufferers. The symptoms appear almost every day and can cause permanent disability, and even death. It disrupts the quality of life and daily activities of the sufferers, as well as decreases their self-reliance in trying to curing the illness. The provision of cognitive-behavioral therapy is expected to increase their quality of life and self-efficacy. The method used in this study was a single case experiment with a single-subject A-B design. Visual analysis was used to analyze the data. The results showed that the quality of life and self-efficacy of the three subjects increased with the effect size score of 0.8. The women with rheumatoid arthritis had improved knowledge about their illness, decreases in pain, fatigue, and relapses; increased ability to manage the symptoms of the illness; and confidence that they could do their daily activities better.